TaD27‐B gene controls the tiller number in hexaploid wheat - Zhao, Bin (Plant Biotechnol J, 2019)
Tillering is a significant agronomic trait in wheat which shapes plant architecture and yield. Strigolactones (SLs) function in inhibiting axillary bud outgrowth. The roles of SLs in the regulation of bud outgrowth have been described in model plant species, including rice and Arabidopsis. However, the role of SLs genes in wheat remains elusive due to the size and complexity of the wheat genomes. In this study, TaD27 genes in wheat, orthologs of rice D27 encoding an enzyme involved in SLs biosynthesis, were identified. TaD27‐RNAi wheat plants had more tillers, and TaD27‐B‐OE wheat plants had fewer tillers. Germination bioassay of Orobanche confirmed the SLs was deficient in TaD27‐RNAi and excessive in TaD27‐B‐OE wheat plants. Moreover, application of exogenous GR24 or TIS108 could mediate the axillary bud outgrowth of TaD27‐RNAi and TaD27‐B‐OE in the hydroponic culture, suggesting that TaD27‐B plays critical roles in regulating wheat tiller number by participating in SLs biosynthesis. Unlike rice D27, plant height was not affected in the transgenic wheat plants. Transcription and gene coexpression network analysis showed that a number of genes are involved in the SLs signalling pathway and axillary bud development. Our results indicate that TaD27‐B is a key factor in the regulation of tiller number in wheat.